Dampak Pandemi Covid-19 Terhadap Pola Prediksi Return Saham Berdasarkan Harga Minyak Dunia - Universe Universe; Hersugondo Hersugondo (Jurnal Ekonomi Pembangunan, 2022)
The Covid-19 pandemic has had a very serious impact, not only on the health sector, but also on the economic sector. Investors cannot predict the effect of a decline or increase in world oil prices during the Covid-19 pandemic on their investment choice decisions. Through this research, an analysis will be carried out on whether Covid-19 will have an influence on the effect of the relationship between world oil prices and stock return predictions using daily Jakarta Composite Index (JCI) data from 03/01/2011 to 14/03/2022. The data to be analyzed will be divided into 3 types of data panels to facilitate the analysis in finding a comparison of the effect of Covid-19 based on a certain period of time. Panel A presents full sample data, Panel B contains pre Covid-19 sample data and Panel C presents data for samples during the time of Covid-19. Based on the results of the study, it can be inffered that the effect of the Covid-19 pandemic can decrase the effectiveness of economic activities and make the capital market unstable, so that the effect of oil prices on stock returns is inaccurate